2021
DOI: 10.3390/s21124198
|View full text |Cite
|
Sign up to set email alerts
|

Monopulse Secondary Surveillance Radar Coverage—Determinant Factors

Abstract: This paper presents a comprehensive study on monopulse secondary surveillance radar (MSSR) coverage. The design and radiation pattern of an improved MSSR antenna is presented herein, highlighting the horizontal and vertical factors of the SUM beam. Moreover, the impact of other determinant factors, such as signal reflection and atmospheric refraction, on the radar coverage were assessed in this work. Real positioning measurement data and coverage simulations were used to support and exemplify theoretical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…And here also as a determinant of MAIN and Standby. The Main will be transmitted through the antenna, and the standby will go into the dummy load (Minteuan et al, 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And here also as a determinant of MAIN and Standby. The Main will be transmitted through the antenna, and the standby will go into the dummy load (Minteuan et al, 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…The name comes from determining the signal's angle from one reply pulse. In SSR systems with monopulses, there is an additional signal known as a difference beam (∆ channel), so it requires three receivers to process information, namely to receive ∆ channel, Ω channel, and ∆ channel (Minteuan et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, the European Union and Federal Aviation Administration have launched Single European Sky Air Traffic Management Research (SESAR) [3] and Next Generation Air Transportation System (NextGen) [4] projects, respectively. In the SESAR and NextGen projects, they use the Automatic Dependent Surveillance-Broadcast (ADS-B) [5] instead of traditional radar surveillance systems, primary and secondary radars [6], [7]. The accuracy in determining aircraft position using ADS-B outperforms primary and secondary radars.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the transportable radar consists of an LVA antenna, which is a fundamental part of the interrogation and acquisition of targets. Reference [2] evaluated the impact of the other determining factors, such as the reflection of the signal and the atmospheric refraction, on the coverage of the radar. Reference [3] found that each existing target will generate several responses from the position that will be obtained, similar to the final one; thus, the objects are called plots, which are displayed on the screen.…”
Section: Introductionmentioning
confidence: 99%